Challenges of nurse managers in creating an environment conducive to empowerment of nurses in mining primary healthcare clinics in South Africa - Sanele E. Nene (Elsevier, 2024)
Background: Nurse managers are expected to create an environment conducive to empowerment of nurses in mining primary healthcare clinics to improve patients' outcomes. However, in a specific mining primary healthcare clinics there are seldom staff trainings and nurses has overwhelming working schedules. Purpose: The aim of the study was to explore and describe the challenges of nurse managers in creating environment conducive to empowerment of nurses in mining primary healthcare clinics in South Africa. Design and Methods: This study was underpinned by Winkler's theoretical framework of leadership roles to create an environment conducive to empowerment. A qualitative, exploratory, descriptive and contextual research design was used to conduct this study in specific mining primary healthcare clinics in South Africa. Individual in-depth interviews were conducted to collect data from ten nurse managers, and Giorgi's thematic analysis method was employed to analyse data. An independent qualitative coder confirmed the study's findings. Trustworthiness was maintained, and ethical principles were also applied throughout the study. Findings: Three themes emerged from the analysed data: (1) training budget challenges; (2) training needs in mining primary healthcare clinics; (3) Legislation, training and development. Discussion and conclusions: There are training budget challenges in mining primary healthcare clinics but nurse managers are not hindered by these challenges in creating an environment conducive to empowerment of nurses.